Intergovernmental Transfers and Political Representation: Empirical Evidence from Argentina, Brazil and Mexico - Moritz Kraemer (Inter-American Development Bank, Office of the Chief Economist, 1997)
Intergovernmental transfers from the central level are an important source of revenue for most subnational governments in developing countries. This importance is likely to grow even further considering ongoing decentralization initiatives in Latin America and elsewhere. This paper investigates whether the transfer of mechanisms in place in Argentina, Mexico, and Brazil satisfy a set of basic propositions: (a) equity principle: poorer jurisdictions are not treated less favorably than better off ones; (b) incentive principle: subnational tax effort is encouraged; and (c) political nondiscrimination principle: electoral, partisan or other political constellations play no role in determining the distribution of transfers. Strikingly, politics do seem to matter. This paper concludes that the political and budgetary institution reform must go hand in hand if a rational system of fiscal federalism is to evolve.
Keywords: 330